Answer:
The first step will be grouping the like terms together on both sides of '='
Explanation:
The given equation is :
![x+7=2x+5-4x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wx2q7w7j4y1k5jw6gia7206kia1ndmsw1b.png)
The first step will be grouping the like terms together on both sides of '='
![x-2x+4x=5-7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/x7enqp0hlv2hprrmeklcybmp4dmm2bclu3.png)
Now adding both sides.
![3x=-2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qgnl9uvbslmim4omniut3er6htbytazfr6.png)
Dividing both sides by 3, we get
![x=(-2)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/7i0wfpn596bex03tjo6vxf0ieloc9i3j6t.png)